PENGEMBANGAN SISTEM PENGGAJIAN YANG TERINTEGRASI DENGAN APLIKASI ARSIP SURAT BERBASIS WEB UNTUK PARA STAF FREELANCER DI CV LOKA MEDIA - Dion Fahrul; Henri Septanto (Pusat Riset dan Inovasi Nasional, 2023)
Database Management is the main job that is part of the development of Information and Communication Technology. Along with the very rapid development of the world of Information and Communication Technology, the data and transaction management system has also experienced developments in its management. In the information age like today, a database management system must be run in a computerized system so that data can be managed better and faster. One of the systems that requires computerization to run better is the payroll system. The purpose of this research is to develop a web-based payroll system that is able to be integrated with mail archive applications so that it can increase the effectiveness of calculating salaries from the work of employees. This study uses the Systems Development Life Cycle method, namely the stages of work carried out by systems analysts and programmers in building information systems and also methods in developing them. This payroll system will be easier and more efficient than the payroll system that has been running before. The results of this study are a payroll system that is integrated with a web-based mail archive application created using the PHP programming language for freelancer staff at CV Loka Media.